Simultaneous Non-Intrusive Monitoring of Environmental Parameters for Standard Time Synchronization as Part of the Westinghouse System of Rating in the Industrial Sector - López-Leyva, Josué Aarón; Franco, Claudia; Martínez, Issac; Dueñas, Rodrigo; García, Mario; Lastra, Samantha; Meza, Oscar; Ponce Camacho, Miguel Ángel (My University, 2019)
This article presents the design and overall performance of a prototype that allows monitoring of some environmental variables in an industrial process in a nonintrusive way. The main objective is to support the Westinghouse methodology and Official Mexican Standards through precise measurements using an integrated and holistic customized prototype. As results, the measurements performance and connectivity status of the prototype are adequate considering short-term testing performed.
Keywords: Prototypes; Monitoring; Temperature measurement; Temperature sensors; Standards; Companies; Campus Ensenada